Genome-Wide Identification and Expression Analysis of Calcium-dependent Protein Kinase in Tomato - Hu, Zhangjian; Lv, Xiangzhang; Xia, Xiaojian; Zhou, Jie; Shi, Kai; Yu, Jingquan; Zhou, Yanhong (Frontiers in Plant Science, 2016)
Calcium-dependent protein kinases (CDPKs) play critical roles in regulating growth, development and stress response in plants. Information about CDPKs in tomato, however, remains obscure although it is one of the most important model crops in the world. In this study, we performed a bioinformatics analysis of the entire tomato genome and identified 29 CDPK genes. These CDPK genes are found to be located in 12 chromosomes, and could be divided into four groups. Analysis of the gene structure and splicing site reflected high structure conservation within different CDPK gene groups both in the exon-intron pattern and mRNA splicing. Transcripts of most CDPK genes varied with plant organs and developmental stages and their transcripts could be differentially induced by abscisic acid (ABA), brassinosteroids (BRs), methyl jasmonate (MeJA), and salicylic acid (SA), as well as after exposure to heat, cold, and drought, respectively. To our knowledge, this is the first report about the genome-wide analysis of the CDPK gene family in tomato, and the findings obtained offer a clue to the elaborated regulatory role of CDPKs in plant growth, development and stress response in tomato.